Micronutrient Selenium: A Pan-India Report on Borderline High - Mehmood, Shahanawaz; Velumani, Amruta; Iyer, Sandhya; Sinkar, Prachi (Asian Journal of Biological and Life Sciences, 2019)
Aim:Selenium is an essential micronutrient and like other nutriments has detrimental health effects in low as well as high levels in the human body. Selenium toxicity is a recorded phenomenon and in this report we aim to present the picture of borderline high selenium levels recorded in a Pan-India cohort.Materials and Methods:Whole blood selenium analysis was done in a cohort of 529,461 individuals inclusive of 284,189 males and 245,272 females respectively. Technology of Inductively Coupled Plasma Mass Spectrometry was used to derive selenium values. Average blood selenium levels were also analyzed. The reporting range of blood selenium is 60 - 340 µg/L. For analysis in this report, 1SD value of > 225 µg/L was considered to be borderline high.Result:The total frequency of borderline high detected in our study was 3.5%. The average blood selenium levels in the borderline high cohort was detected to be 256 +/- 33 µg/L. Geographic prevalence analysis highlighted maximum to be from the North and North-Western region.Conclusion:Our report is one of the few to highlight not alone the frequency of borderline selenium in Pan-India level, but also identify geographical regions of concern. Such analysis will aid in devising region-specific supplementation program to avoid over dosing.
Keywords: Selenium; Borderline high; India; Toxicity